Coincidence point and invariant approximation for mappings satisfying generalized weak contractive condition - Mujahid Abbas; Ismat Beg (Fixed Point Theory and Applications, 2006)
We prove the existence of coincidence point and common fixed point for mappings satisfying generalized weak contractive condition. As an application, related results on invariant approximation are derived. Our results generalize various known results in the literature.